2012
DOI: 10.18584/iipj.2012.3.1.6
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Indigenous Research Guidelines to Inform Genomic Research in Indigenous Communities

Abstract: BACKGROUND: Genetic research has potential benefits for improving health, such as identifying molecular characteristics of a disease, understanding disease prevalence and treatment, and developing treatments tailored to patients based on individual genetic characteristics of their disease. Indigenous people are often targeted for genetic research because genes are easier to study in communities that practice endogamy. Therefore, populations perceived to be more homogenous, such as Indigenous peoples, are ideal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…First, there are few examples of ethical guidelines in practice within research projects; therefore, Indigenous communities continue to be negatively impacted by some contemporary and current research projects (Taniguchi, Taualii, & Maddock, 2012;Tobias et al, 2013). To address this problem, researchers have called for more guidance regarding specific aspects of the research process, such as explicitly addressing how informed consent can be effectively and appropriately obtained in Indigenous communities in accordance with both research ethics guidelines and community customs and practices (Sherman et al, 2012).…”
Section: Challenges Associated With the Application Of Ethical Princimentioning
confidence: 99%
“…First, there are few examples of ethical guidelines in practice within research projects; therefore, Indigenous communities continue to be negatively impacted by some contemporary and current research projects (Taniguchi, Taualii, & Maddock, 2012;Tobias et al, 2013). To address this problem, researchers have called for more guidance regarding specific aspects of the research process, such as explicitly addressing how informed consent can be effectively and appropriately obtained in Indigenous communities in accordance with both research ethics guidelines and community customs and practices (Sherman et al, 2012).…”
Section: Challenges Associated With the Application Of Ethical Princimentioning
confidence: 99%
“…Many tribes and Alaska Native groups have also established research review processes that include protocols for data ownership and management agreements. 41 …”
Section: Moving Forwardmentioning
confidence: 99%
“…A recent comprehensive international review and comparative analysis of Indigenous research guidelines in New Zealand, Australia, Canada, and the United States (US) identified a number of areas of concern and a need for further work in developing research policy that promotes respectful engagement with Indigenous communities (Taniguchi, Taualii, & Maddock, 2012). In New Zealand, Australia, and the US, there is currently no direction to seek community engagement during the development of research protocols as there is in Canada, although all countries did provide some guidance in other areas of community consultation (Taniguchi et al, 2012) More specifically, New Zealand research guidelines do not stipulate a requirement to define potential uses prior to sample collection, to make provision for individual or community withdrawal of samples, to discuss secondary uses with contributing individuals or communities, or to obtain community approval for secondary uses of material or the resulting genetic data (Taniguchi et al, 2012), although researchers may opt to do so.…”
Section: Engagement With Māori Through Research Partnershipsmentioning
confidence: 99%
“…In New Zealand, Australia, and the US, there is currently no direction to seek community engagement during the development of research protocols as there is in Canada, although all countries did provide some guidance in other areas of community consultation (Taniguchi et al, 2012) More specifically, New Zealand research guidelines do not stipulate a requirement to define potential uses prior to sample collection, to make provision for individual or community withdrawal of samples, to discuss secondary uses with contributing individuals or communities, or to obtain community approval for secondary uses of material or the resulting genetic data (Taniguchi et al, 2012), although researchers may opt to do so. Furthermore, there is no direction around prioritization of research uses such that the research should benefit the contributing population, or a requirement that a clear position on commercial applications be disclosed.…”
Section: Engagement With Māori Through Research Partnershipsmentioning
confidence: 99%